Effect of extracellular polymeric substances on the colony size and morphological changes of Microcystis - Pan, Jiaxin; Yang, Zhongyong; Hu, Nan; Xiao, Bangding; Wang, Chunbo; Wu, Xingqiang; Yang, Tiantian (Frontiers in Plant Science, 2024)
Surface blooms of colony-forming Microcystis are increasingly occurring in aquatic ecosystems on a global scale. Recent studies have found that the Microcystis colonial morphology is a crucial factor in the occurrence, persistence, and dominance of Microcystis blooms, yet the mechanism driving its morphological dynamics has remained unknown. This study conducted a laboratory experiment to test the effect of homologous EPS on the morphological dynamics of Microcystis. Ultrasound was used to disaggregate colonies, isolating the cells and extracellular polymeric substances (EPS) of the Microcystis suspension. The single cells were then re-cultured under three homologous EPS concentrations: group CK, group Low, and group High. The colonies' size, morphology, and EPS (including tightly bound EPS (TB-EPS), loosely bound EPS (LB-EPS), bound polysaccharides (B-Polysaccharides), and bound protein (B-Protein)) changes of colonies were closely monitored over a period of 2 months. It was observed that colonies were rapidly formed in group CK, with median colony size (D50) reaching 183 µm on day 12. And the proportion of colonies with a size of 150-500 µm increased from 1% to more than 50%. Colony formation was also observed in both group Low and group High, but their D50 increased at a slower rate and remained around 130 µm after day 17. Colonies with a size of 50-150 µm accounts for more than 50%. Group CK and group Low successively recovered the initial Microcystis morphology which is a ring structure formed of several small colonies with a D50 of 130 µm. During the recovery of the colony morphology, the EPS per cell increased and then decreased, with TB-EPS and B-Polysaccharides constituting the primary components. The results suggest that colony formation transitioned from adhesion-driven to being division-driven over time. It’s suggested that the homologous EPS released into the ambient environment due to the disaggregation of the colony is a chemical cue that can affect the formation of colony. This plays an important but largely ignored role in dynamics of Microcystis and surface blooms.